PENGARUH KEPEMIMPINAN KASAT RESKRIM TERHADAP KINERJA ANGGOTA SATUAN RESERSE KRIMINAL POLRES CIREBON KOTA: The Effect Of Criminal Investigation Unit Leadership On The Performance Of Criminal Investigation Unit Members At Cirebon City Police Department - Rajasa Wahyu Abadi; Ade Setiadi; Erna Erna (Jurnal Investasi, 2026)
This study analyzes the influence of the Head of Criminal Investigation Unit leadership on the performance of members of the Criminal Investigation Unit at Cirebon City Police Resort. The study applies an explanatory survey method with a quantitative approach. The population consisted of 38 criminal investigation personnel, and all of them were included as the sample through total sampling. Leadership was measured through four functions, namely innovator, communicator, motivator, and controller. Performance was measured through work quality, timeliness, initiative, capability, and communication. Data were collected through observation, interviews, documentation, and questionnaires. Instrument testing reported in the thesis indicates that all items are valid and reliable. Path analysis was employed to examine the simultaneous effect of leadership and the contribution of each leadership dimension to member performance. The findings show that the leadership of the Head of Criminal Investigation Unit is categorized as good, with an average score of 69.80 percent or a rating value of 3.52, while member performance is categorized as fairly good, with an average score of 67.37 percent or a rating value of 3.29. Simultaneously, leadership affects member performance by 67.45 percent, while the remaining 32.55 percent is explained by other factors outside the model. In the thesis model, the largest total contribution comes from the controller function, followed by motivator, innovator, and communicator functions. These results indicate that supervisory strength, internal coaching, communication quality, and the leader ability to direct organizational resources are crucial to improving the performance of criminal investigation personnel.